Mu Opioid Receptor Heterodimers Emerge as Novel Therapeutic Targets: Recent Progress and Future Perspective - Zhang, Li; Zhang, Jiang-Tao; Hang, Lihua; Liu, Tong (Frontiers in Pharmacology, 2020)
Opioids are the most effective analgesics used in the clinical management of cancer pain or non-cancer pain. However, chronic opioids therapy can cause many side effects including respiratory depression, nausea, sedation, itch, constipation, analgesic tolerance, hyperalgesia, high addictive potential, and abuse liability. Opioids exert their effects through binding to the opioid receptors belonging to the G-protein coupled receptors (GPCRs) family, including μ-opioid receptor (MOR), -opioid receptor (DOR), and κ-opioid receptor (KOR). Among them, MOR is essential for opioid-induced analgesia and also responsible for adverse effects of opioids. Importantly, MOR can form heterodimers with other opioid receptors and non-opioid receptors in vitro and in vivo, and has distinct pharmacological properties, different binding affinities for ligands, downstream signaling, and receptor trafficking. This mini review summarized recent progress on the function of Mu opioid receptor heterodimers, and we proposed that targeting Mu opioid receptor heterodimers may represent an opportunity to develop new therapeutics, especially for chronic pain treatment.